Whistler wave emission by a modulated electron beam on a metal-plasma boundary - Anisimov, І.О.; Kelnyk, О.І.; Krafft, C.; Nychyporuk, T.V. (Вопросы атомной науки и техники, 2003)
The transition radiation of a thin modulated electron beam injected from a conducting plane into a plasma along an arbitrary magnetic field normal to that plane is calculated. The radiation field is formed as a result of the interference of three waves with different wave vectors. The radiation pattern is mainly determined by one of those waves, depending on the parameters of the model.